Willingness of Older Korean-American Adults to Use Hospice - Jang, Yuri (2010)
Responding to an urgent need for more research on end-of-life concerns of racial and ethnic minorities, the present study explored predictors of willingness of older Korean-American adults (N = 675) to use hospice. Guided by Andersen's behavioral health model, the study considered predisposing factors (age, sex, marital status, education), potential health needs (chronic conditions, functional disability), and enabling factors (health insurance, acculturation, prior awareness of hospice). Nearly three-quarters of the sample answered yes to the following statement and question, “Hospice is a program that helps people who are dying by making them feel comfortable and free of pain when they can no longer be cured of their disease. If you needed hospice services, would you use them?” A greater willingness was observed in younger persons (odds ratio (OR) = 0.96, 95% confidence interval (CI) = 0.93–0.98) and those with higher levels of education (OR = 1.67, 95% CI = 1.12–2.48), more chronic conditions (OR = 1.23, 95% CI = 1.05–1.44), health insurance (OR = 0.59, 95% CI = 0.37–0.94), higher levels of acculturation (OR = 1.07, 95% CI = 1.03–1.10), and prior awareness of hospice (OR = 4.43, 95% CI = 2.85–6.90). The present study highlights the role of prior awareness in shaping individuals’ attitudes toward services, calling attention to a need for community education and outreach programs for racial and ethnic minorities, with specific emphasis on dissemination of information and greater awareness of hospice services.